Analysis Of Nagari Financial Management to Improve Community Welfare in Nagari Sicincin District 2X11 Six Lengkung Padang Pariaman Regency - Hartika, Yoli; Parsaulian, Baginda (Pascasarjana Universitas Pasundan, 2023)
Nagari is a form of unity of customary (conventional) citizens who have free authority and carry out their orders and are specifically located in the Minangkabau ethnic area. The independence of the Nagari region is based on the Minangkabau cultural system which has a different form of custom that has been passed down from generation to generation. This comparison stems from the characteristics of Nagari as a